Responsibility of the Company's Board of Directors as Perpetrators of Corruption Crimes in Case Decision Number: 17/Pid.Sus-Tpk/2020/Pn.Plk - Jumadi Jumadi; Zudan Arief Fakrulloh (International Journal of Social Service and Research, 2026)
Corruption in Indonesia increasingly involves corporations beyond individual perpetrators, with limited liability companies frequently implicated in criminal acts despite their status as legal entities under Law Number 40 of 2007. This research examines the criminal liability of corporate owners through a case study of Didie, SE, owner of CV. Liting Perkasa, who was convicted in Decision Number 17/Pid.Sus-TPK/2020/PN.Plk for corruption in a road construction project in Katingan Regency, Central Kalimantan. The study analyzed the application of corporate criminal liability theory to this case, particularly examining whether the defendant's actions constitute corporate or individual criminal responsibility. Employing normative juridical research methods with statutory and conceptual approaches, this study analyzes legal norms, principles, doctrines, and applicable legislation relevant to corporate criminal liability. The findings reveal that the defendant can be classified as capable of being responsible under the theory of corporate criminal liability, as the criminal act was committed through the corporate entity CV. Liting Perkasa. The Panel of Judges correctly declared the defendant legally and convincingly guilty of corruption causing state financial losses. The analysis further indicates that if CV. Lintang Perkasa is considered a corporation, the responsibility imposed should refer to strict liability, which allows criminal responsibility without proving fault on the perpetrator's part. This principle is particularly relevant in corporate crimes where proving individual intent or negligence is challenging.